Effect of Lepidium meyenii on in vitro fertilization via improvement in acrosome reaction and motility of mouse and human sperm - Yusuke Aoki (Reproductive Medicine and Biology, 2019)
Abstract Purpose The direct effects of Lepidium meyenii (Maca) on sperm remain unclear. Herein, we examined the direct effect of Maca on in vitro fertilization. Methods We examined the fertilization rate in a mouse model and the rate of acrosome reaction in sperm from transgenic mice expressing enhanced green fluorescent protein (EGFP) in a Maca extract‐containing human tubal fluid (HTF) medium. Using human sperm, we assessed acrosome status via fluorescein isothiocyanate‐conjugated peanut agglutinin (FITC‐PNA) staining and performed detailed analysis using a sperm motility analysis system (SMAS). Results In the mouse model, the fertilization rate in the Maca extract‐containing HTF was significantly higher than that in the control medium. The acrosome reaction rate in sperm from transgenic mice expressing EGFP was also significantly higher in the Maca extract‐containing HTF than that in the control medium. Similarly, a high acrosome reaction rate, identified via FITC‐PNA staining of human sperm samples, was found in the Maca extract‐containing HTF compared with that in the control medium. Human sperm motility in the Maca extract‐containing HTF was also increased compared with that in the control medium as measured using an SMAS. Conclusions Maca improved in vitro fertilization rates by inducing an acrosome reaction and increasing sperm motility.